Assessment of maternal risk indicators for the development of caries in their children: A comparative, cross-sectional study - H R Priyadarshini; Bennete Aloysius Fernandes; S S Hiremath; Avita Rath; Vanishree Shivakumar; Anand Siddappa Tegginamani (Wolters Kluwer Medknow Publications, 2017)
Introduction: Certain factors in mothers could be risk indicators for certain diseases in their children. Hence, this study was undertaken to assess maternal risk indicators for the development of early childhood caries in their children. Methodology: A comparative, cross-sectional study was designed among 180 mother-child pairs attending various Anganwadi centers. Demographic, dietary, oral hygiene practices and other necessary information were collected from mothers using a structured questionnaire. Caries status and amount of plaque were recorded through clinical examination. Nonstimulated saliva from mothers was cultured for mutans streptococci (MS). Data were analyzed using SPSS version 17. Chi-square, Student's t-test, and logistic regression were used. A P ≤ 0.05 was considered statistically significant. Results: In the study group, 73.3% of mothers had caries as compared to only 53.3% mothers in control group. While mean DMFT and mean DMFS of mothers in the study group was 3.78 ± 3.91 and 8.37 ± 12.2, respectively, the same for the mothers in the control group was 2.66 ± 3.01 and 5.8 ± 5.3. Sixty (66.7%) out of ninety mothers in the study group had a high MS count as compared to only 40 (44.4%) mothers in control group (P = 0.003). Conclusion: The present study showed that high salivary MS count and decay in mothers could be important risk indicators for the development of caries in their children.